Post-orthodontic recontouring of anterior teeth using composite injection technique with a digital workflow - Hosaka, Keiichi; Tichy, Antonin; Motoyama, Yasuji; Mizutani, Koji; Lai, Wei-Jen; Kanno, Zuisei; Tagami, Junji; Nakajima, Masatoshi (Journal of esthetic and restorative dentistry, 2020)
OBJECTIVE: Restorative treatment of anterior teeth is often required as the final step of orthodontic therapy to optimize the esthetics and function. This case report presents a direct minimally invasive approach for post-orthodontic recontouring of anterior teeth using the composite injection technique with a digital workflow. CLINICAL CONSIDERATIONS: The extraction of central incisors with short roots was indicated to resolve maxillary anterior crowding. The gained space was closed with lateral incisors, and it was necessary to recontour them and canines to resemble central and lateral incisors, respectively. The restorations were digitally designed, and a transparent silicone index was fabricated from a 3D-printed cast of the digital wax-up. After lateral incisors and canines were bonded with a universal adhesive in the etch-and-rinse mode, a highly filled injectable composite resin was applied into the index. The restorative treatment was preceded by gingivectomy using an Er:YAG laser and home bleaching. CONCLUSIONS: In cases where more complex recontouring of anterior teeth is necessary, the composite injection technique could be a suitable alternative to indirect restorations, because it is straightforward, cost-effective, and does not require any preparation. The digital workflow simplified and expedited the treatment while contributing to its precision. CLINICAL SIGNIFICANCE: Post-orthodontic recontouring using direct composite restorations is well accepted by patients due to low cost and non-invasiveness. However, in complicated cases, the free-hand technique is time-consuming and technique-sensitive. The presented composite injection technique with a digital workflow significantly simplifies and expedites the composite placement while predictably enhancing the treatment outcome.
Keywords: Incisor; Dental Restoration, Permanent; digital dentistry; Composite Resins; Esthetics, Dental; řezáky; bleaching; složené pryskyřice; estetika stomatologická; Humans; periodontics/orthodontics; trvalá zubní náhrada; lidé; operative dentistry; průběh práce; CAD/CAM; Workflow